ANALISIS KOMPARATIF RITUAL MENGHORMATI ARWAH LELUHUR OBON MATSURI (お盆祭り) DAN FESTIVAL NYADRAN - Satrio Wibowo, Franky; Dr.Marisa Rianti, S.S., M.Hum (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2022)
Culture is an inseparable part of a country. It is through the ancestors that culture is passed down from generation to generation. Japan has a culture of welcoming the arrival of ancestral spirits and bringing back ancestral spirits back to their world which is commonly called Obon Matsuri. Meanwhile, Indonesia has a culture to visit the graves of ancestral spirits by bringing offerings. The culture of the Javanese people is called the Nyadran Festival. Both the Obon Matsuri and the Nyadran Festival both have rituals that are meaningful as symbols of respect for ancestral spirits and expressions of gratitude to God. Obon Matsuri, for example, has the ohakamairi (お墓参り) ritual, which is the activity of cleaning the graves of ancestral spirits. It is similar to the Nyadran Festival which has a ritual of cleaning the graves of ancestral spirits called nyekar. Praying for ancestral spirits who are believed by the Japanese and Javanese people to have a life in another world makes rituals performed at the Obon Matsuri and Nyadran Festival routinely carried out. By carrying out the ceremony, it indirectly maintains vertical relationships (humans with others or humans with the universe) and horizontal relationships (humans with God). Keywords: obon, nyadran, matsuri